The Study of Settlement Preservation Pattern for Environmental Sustainability in Canggu Village, Badung Regency, Bali Province - Nurjani, Ni Putu Suda (Green Publisher Indonesia, 2024)
Canggu is one of the settlements Village in the southern coastal community in Bali which is currently experiencing very rapid tourism development. This village has a relatively flat topographic condition, as well as being one of the areas of Majapahit descent. The rapid development of tourist accommodation that currently occurs in Canggu, has an impact on the high conversion of land use, and the disruption of local community settlements. Seeing this fact, it is considered necessary to make an evaluation study on the development of spatial planning which will later be used as input in determining spatial land use control policies in Canggu Village. This research uses qualitative methods, case studies using field observation techniques and interviews, which are then compared with literature reviews in the form of regional spatial policy studies and relevant theories. The analysis was conducted on the residential area of Canggu Village, which aimed to determine the main causes of land use change and displacement of local community settlements. From the results of the analysis, which is then compared with literature studies, it is expected to be able to find a solution to preserve the urgency of local community settlements. The results of the analysis show that the implementation of spatial concepts sourced from culture is more respected by the community compared to local government policies. The hulu-teben concept as the basis for the preservation of settlement spatial values derived from the Tri Hita Karana cultural philosophy, is considered very effective and feared by the community because it is related to social sanctions that must be borne by the community, which are outlined in pararem.